READINESS LECTURER FACULTY OF LAW IN THE ERA COMPETITION ECONOMIC COMMUNITY ASEAN - Halimatul Maryani (NOMOI Law Review, 2021)
The background ofthis article is written thatIndonesia and Southeast Asian countries are already within the scope of theAsean Community.So each country must prepare human resources (HR) lecturers in the competition of the labor market in the Southeast Asian region.Given the increasingly fierce competition, of course it requires the expertise of a workforce (lecturers)who are ready to be competitive, of courseIn this era of globalization of international competition. The purposeof this study was to examine the role and readiness of lecturers in competition in the era of the international economic community, with themethodused in this research is the normative juridical method andits useto encourage lecturers to be more active in implementing the Tri Dharma of Higher Education.As aconclusion, lecturers are obliged to carry out the tri dharma of higher education and play a very important role in the development of higher education institutions, especially the respective universities they doand each lecturer isadvisedto apply the results of their performance in the lecture material.Keywords:Readiness,Lecturer, International Competition, MEA.